Comparison of circular and elliptical geometric models with optimal two-dimensional imaging view for Doppler quantification of mitral regurgitant volume in older patients - Wu-Gang Wang; Ning Zhang; Miao-Miao Pei; Xue-Jia Guo; Gai-Qin Liu; Yan-Dong Deng (Frontiers in Cardiovascular Medicine, 2026)
Background Doppler volumetric quantification of mitral regurgitation (MR) depends on accurate stroke-volume estimation, but simplified assumptions regarding mitral annular area may introduce view-dependent error, particularly in older patients. This study evaluated whether circular versus elliptical annular models and standard two-dimensional (2D) imaging views influence Doppler-derived regurgitant volume (RVol) and effective regurgitant orifice area (EROA), using three-dimensional (3D) echocardiographic reference measures. Methods In this retrospective study, 286 older patients with MR in sinus rhythm underwent transthoracic echocardiography with 2D imaging and pulsed-wave and continuous-wave Doppler, transthoracic 3D color Doppler imaging, and three-dimensional transesophageal echocardiography (3D TEE) for mitral annular imaging. Six prespecified combinations of 2D view and geometric model were used to estimate mitral annular cross-sectional area (CSA), RVol, and EROA. These included three circular models based on the parasternal long-axis (PLAX), apical four-chamber (A4C), or apical two-chamber (A2C) view and three elliptical models combining pairs of these views. Reference measures included 3D planimetric EROA (EROA₃D) and 3D-derived RVol (RVol₃D), calculated as EROA₃D multiplied by the MR velocity–time integral (MR VTI). Agreement was assessed using Bland–Altman analysis. Results Mitral annular diameters differed among views (A4C > A2C > PLAX; P < 0.001). Compared with 3D TEE planimetry, elliptical CSA estimates showed smaller biases and narrower limits of agreement than circular estimates, with the A4C + A2C elliptical model showing the most favorable agreement. For the primary outcomes, the PLAX circular strategy underestimated both RVol and EROA, with biases of −10.8 mL and −0.080 cm 2 , respectively (both P < 0.001). The A4C + A2C elliptical strategy showed near-zero bias and the narrowest limits of agreement for both RVol (bias, −0.6 mL; P = 0.317) and EROA (bias, −0.005 cm 2 ; P = 0.209), with consistent performance across MR mechanisms and severity strata. Conclusions In older patients, Doppler-based MR quantification is sensitive to mitral annular geometric modeling and 2D view selection. An elliptical model integrating A4C and A2C diameters showed the most consistent agreement with 3D reference measures and may improve the standardization of Doppler-based MR assessment.